Households and Heat Stress : Estimating the Distributional Consequences of Climate Change - Park, Jisung; Hallegatte, Stephane; Bangalore, Mook; Sandhoefner, Evan (World Bank, Washington, DC, 2015)
Recent economic research documents a range of adverse welfare consequences from extreme heat stress, including health, labor productivity, and direct consumption disutility impacts. Without rapid adaptation, climate change will increase the burden of heat stress experienced by much of the world’s population in the coming decades. What will the distributional consequences of this added heat stress be, and how might this affect optimal climate policy? Using detailed survey data of household wealth in 690,745 households across 52 countries, this paper finds evidence suggesting that the welfare impacts of added heat stress caused by climate change may be regressive. Specifically, the analysis finds that poorer households tend to be located in hotter locations across and within countries, and poorer individuals are more likely to work in occupations with greater exposure to the elements not only across but also within countries. These findings—combined with the fact that current social cost of carbon estimates do not include climate damages arising from the productivity impacts of heat stress—suggest that optimal climate policy, especially when allowing for declining marginal utility of consumption, involves more stringent abatement than currently suggested, and that redistributive adaptation policies may be required to reduce the mechanical inequities in welfare impacts arising from climate change.